PERANCANGAN SISTEM INFORMASI BANK MINI SISWA SMK DIPONEGORO BANYUPUTIH DENGAN METODE CASH BASIS - Rosita Maharditia (Jurnal Ilmiah Sistem Informasi, 2024)
Based on the problems currently being faced by Vocational School Diponegoro Banyuputih, one of which is the problem of student savings, the system has been running for 4 years. In the current system, the student savings system at Diponegoro Vocational School is still done manually. If you remember the importance of processing data and information in this system, of course this is felt to be less effective and efficient in terms of problems that arise, so it is necessary to design a computerized system. The aim of this research is to ease the performance of savings administrators in processing data, recording data and making reports on this savings information system so that errors that are often experienced can be resolved, designing and building a financial recapitulation system that directly produces financial reports, creating a financial information system using the Cash method. A suitable base for daily management. System analysis and design is preceded by system development which includes system identification, data and information identification. This system development model is used to describe the system being designed, namely the actual situation. The resulting program was built using the PHP (Hypertext Preprocessor) programming language with a MySQL database. It is hoped that the implementation of the resulting system will facilitate data management quickly and accurately and the preparation of financial reports